Are Donor Countries Giving More or Less Aid? - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2006)
The volume of foreign aid has increased during the last four decades, albeit with interruptions in certain years. Over time, the major recipients have changed: while the share of aid to Asia has diminished since the 1980s, that destined for sub-Saharan Africa has grown. There is some evidence that, since the late 1990s, debt relief has assumed a larger share of the increased aid flows to sub-Saharan Africa. The share of technical cooperation-a component of aid that is viewed as being driven by donors-has risen. More recently, there has been an increased emphasis on providing budget support to recipient governments, especially in the form of debt relief. Donor harmonization, national ownership of development plans, and sound policies on the part of the recipients are crucial for the aid to be effective in reducing poverty.